2019
DOI: 10.1186/s12906-019-2517-5
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of safety and potential of black hellebore extracts for cancer treatment

Abstract: Background The therapeutic use of Helleborus niger L. is manifold due to its specific phytochemical composition. Two compound groups, the ranunculin derivates including protoanemonin and the steroidal saponins, are also associated with toxicity (genotoxicity, disintegration of membrane structures). Therefore, in vitro investigations were performed on safety aspects of a Helleborus niger aqueous fermented extract ( HNE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…[24][25][26] Moreover, a recent preclinical evaluation showed that black hellebore extracts are safe and have potential for cancer treatment. 27 This finding was supported by two independent studies, which both found that the proliferation of tumor cells can be inhibited by Helleborus niger root and whole plant extracts. 28,29 The chemistry of the active ingredients in the above-ground parts of Helleborus niger has been investigated in a few studies.…”
Section: Introductionmentioning
confidence: 73%
“…[24][25][26] Moreover, a recent preclinical evaluation showed that black hellebore extracts are safe and have potential for cancer treatment. 27 This finding was supported by two independent studies, which both found that the proliferation of tumor cells can be inhibited by Helleborus niger root and whole plant extracts. 28,29 The chemistry of the active ingredients in the above-ground parts of Helleborus niger has been investigated in a few studies.…”
Section: Introductionmentioning
confidence: 73%
“…A similar study by Felenda et al evaluated the antitumor effect of H. niger on several tumor cell lines, including melanoma and breast cancer. The results revealed that H. niger has a concentration-dependent cytotoxic and antiproliferative effect on all lines used [20]. In addition, Schink and colleagues highlighted the cytotoxic effect of H. niger extract on the melanoma cell line due to its ability to induce cell apoptosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…12–14 Recent findings indicate that Helleborus root extracts are safe and possess the potential for cancer treatment. 15 Furthermore, extracts of roots and the whole plant have been shown to inhibit the proliferation of tumor cells. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Recent findings indicate that Helleborus root extracts are safe and possess the potential for cancer treatment. 15 Furthermore, extracts of roots and the whole plant have been shown to inhibit the proliferation of tumor cells. 16,17 In the 16th century, the Swiss physician and alchemist Paracelsus described Christmas Rose leaves as a dementia preventative par excellence.…”
Section: Introductionmentioning
confidence: 99%